Forum on stigma, discrimination, and health: policies and research challenges. Introduction Fórum: estigma, discriminação e saúde: desafios políticos e acadêmicos. Introdução - Simone Monteiro; Wilza Vieira Villela (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This introduction outlines the Forum on stigma, discrimination, and health: policies and research challenges, including four articles and a final commentary. The first article reviews the development of international research on the relationship between discrimination and health. The second analyzes the recent Brazilian research output on AIDS, stigma, and discrimination. The third article addresses conceptual and methodological aspects of the relations between discrimination and health from an epidemiological perspective. The forth examines the process of affirming sexual rights in Brazil, involving the judiciary system, public policies, and the executive and legislative branches of government, among others. The fifth paper presents comments and questions on the contents discussed in the first four articles. The reflections aim to provide conceptual and methodological contributions for research and health policies on stigma and discrimination, given the gaps identified in the international and Brazilian literature. Esta introdução apresenta o Fórum: "estigma, discriminação e saúde: desafios políticos e acadêmicos", com quatro artigos e um comentário final. O primeiro artigo discute o desenvolvimento da pesquisa internacional sobre as interseções entre discriminação e saúde. O segundo analisa a produção acadêmica nacional recente sobre AIDS, estigma e discriminação. O terceiro discute aspectos conceituais e metodológicos das relações entre discriminação interpessoal e agravos de saúde nos estudos epidemiológicos. O quarto examina o processo de afirmação dos direitos sexuais no Brasil que envolve o sistema judiciário, políticas públicas e as esferas executivas e legislativas do Estado, entre outros. O quinto trabalho tece considerações e questionamentos sobre os conteúdos apresentadas nos quatro artigos. As reflexões visam fornecer aportes conceituais e metodológicos para pesquisas e políticas em saúde sobre a produção do estigma e da discriminação, haja vista as lacunas sobre o tema na produção acadêmica nacional e internacional.